2015
DOI: 10.5664/jcsm.5270
|View full text |Cite
|
Sign up to set email alerts
|

Unpacking Sleep and Suicide in Older Adults in a Combined Online Sample

Abstract: BRIEF SUMMARYCurrent Knowledge/Study Rationale: Research has shown relations between duration of insomnia symptoms/duration of nightmares and suicide risk in younger adults. However, this relation has not been examined in older adults. Study Impact: The present study found that, in older adults, nightmare duration was related to suicide risk independent of current nightmares, current symptoms of and duration of insomnia, and symptoms of anhedonia and PTSD. Nightmare duration was also related to suicide risk in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 46 publications
3
57
1
Order By: Relevance
“…Collectively, findings from these studies indicated that sleep problems were related to suicidality, independent of acquired capability for suicide (Golding et al, 2015, Nadorff et al, 2014). Hochard et al (2016) proposed alternative hypotheses whereby acquired capability was posited to interact with both severity of insomnia symptoms and the frequency and intensity of nightmares, to predict suicidal thoughts.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Collectively, findings from these studies indicated that sleep problems were related to suicidality, independent of acquired capability for suicide (Golding et al, 2015, Nadorff et al, 2014). Hochard et al (2016) proposed alternative hypotheses whereby acquired capability was posited to interact with both severity of insomnia symptoms and the frequency and intensity of nightmares, to predict suicidal thoughts.…”
Section: Resultsmentioning
confidence: 86%
“…2; Chu et al, 2016, Golding et al, 2015, Littlewood et al, 2016, Nadorff et al, 2014). This is in agreement with findings from the broader literature.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that interpersonal theory constructs, including thwarted belongingness, may serve as an explanatory link between insomnia and suicide risk. Consistent with this assertion, a study of older adults also revealed that insomnia symptoms were no longer related to suicide risk after controlling for interpersonal theory variables (Golding et al, 2015). However, these equivocal results emphasize the need for further investigation into the relationship between these symptom constellations.…”
Section: Introductionmentioning
confidence: 81%
“…An association between sleep problems and suicidal behaviors has been widely documented [1719]. But systematic analyses of insomnia and suicide-related thoughts and behaviors are still inconsistent across studies and there is a lack of empirical studies focusing on mediating factors in the insomnia and suicide relationship [20].…”
Section: Introductionmentioning
confidence: 99%